Prevalence of sexual dysfunction in women with cancer: A systematic review and meta-analysis - Seyedeh Esmat Hosseini; Mahnaz Ilkhani; Camelia Rohani; Alireza Nikbakht Nasrabadi; Raza Ghanei Gheshlagh; Ashraf Moini (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Cancer is one of the most common diseases and it has many physical and psychological consequences. Women with cancer are more likely to suffer from sexual dysfunction (SD) than healthy women. Objective: To estimate the overall prevalence of SD in women with cancer. Materials and Methods: The international databases Google Scholar, Embase, PubMed, Web of Science, and Scopus were searched for related articles without any time limitation. The keywords "Neoplasia", "Tumor", "Cancer", "Malignancy", "Female Sexual Function Index", "FSFI", and "female sexual dysfunction" along with their combinations were used in the search. Inconsistencies in the data were examined using the I2 test. The data were analyzed using the meta-analysis method and the random-effects model in the Stata software. Results: The analysis of 24 articles with a sample size of 5483 women showed that the prevalence of SD in women with cancer was 66% (95% CI: 59-74%). The highest and lowest prevalence were in Africa and Europe, respectively (75%; 95% CI: 66-83% vs. 43%; 95% CI: 26-60%, respectively). There was no relationship between the prevalence of SD and the mean age of the women, sample size, yr of publication, or quality of articles. Conclusion: SD is highly prevalent in women with cancer. African and American women with cancer have a higher average SD prevalence than Asian and European ones.